BRISP, a new small-angle time-of-flight neutron spectrometer to study collective dynamics in disordered matter - Orecchini, A.; Pilgrim, W.-C.; Petrillo, C.; Suck, J.-B.; Sacchetti, F. (Condensed Matter Physics, 2008)
An outline is given of the new neutron Brillouin Spectrometer BRISP which was installed during the last years and recently became fully operational at the Institute Laue-Langevin in Grenoble (France). The main technical features are described and some of the first experimental results are presented, demonstrating the present capabilities of this new-type inelastic small-angle spectrometer. Future upgrades are foreseen and expected to further improve the instrument performances.